Evaluation of Strategic Optimization of Housing and Settlement Planning in Balikpapan with Integration EWM-DEA - Christopher Davito Prabandewa Hertadi; Firly Eryun Desita Safitri; Ahmad Jamil; Putri Gesan Prabawa Anwar; Healty Susantiningdyah; Windi Auliana (Universitas Islam Raden Rahmat, Malang, 2026)
Rapid population growth, limited developable land, and rising housing demand create increasing pressure on the urban settlement system in Balikpapan. This study aims to develop a comprehensive model to support sustainable housing planning by examining the interactions among social, economic, and environmental factors. The study gave strategic optimization in housing and setllement planing in Balikpapan with social, economic, and environmental consideration. A system dynamics model was constructed using causal loop and stock–flow structures to simulate system behavior from 2020 to 2050. Indicator performance was assessed using an entropy-based weighting method, while efficiency was evaluated through a data envelopment analysis approach. Three policy scenarios were tested: economic growth, development of public rental housing, and a combined strategy. The results of the study indicate that the environmental output variable (green open space) experienced a significant decline from 696,800 hectares to 390,599.6 hectares. The results also show that environmental indicators consistently achieved the highest performance, followed by social indicators, while economic indicators remained the weakest due to high development costs. Therefore, recommendations for improvements in the environmental sector can provide better output results. The scenario focused on vertical public housing provides the most balanced outcome, improving social welfare while reducing pressure on land resources. These findings emphasize the importance of integrated policy planning that aligns effectiveness and resource efficiency to support sustainable urban development.